Joyful Learning Model Using Educational Cinema to Develop Disaster Awareness Among Elementary Students - Setyawati, Sri Panca; Hartati, Merri Sri; Cendana, Wiputra; Sayekti, Siskha Putri; Ridwan, Mochamad (Universitas Sarjanawiyata Tamansiswa, 2023)
Indonesia as one of the disaster-prone countries needs to prepare a society that is strong disaster. Response to disasters must be fostered early. One effort to foster public awareness of the potential of disasters is through education. This study aims to build funding awareness of elementary school students through learning activities with the joyful learning model using educational cinema. Research conducted using a quantitative approach with an one-shot-case study design and research subjects totaling 107 elementary school students. Data were analyzed by descriptive statistical techniques. The findings of this study are: 1) The level of awareness of students in the medium category and 2) students show enthusiastic attitudes to participate in learning with Joyful Learning using educational cinema. Learning uses a joyful learning model with educational cinema according to elementary school students because during learning students feel enjoy. Such learning situations make students not feel depressed so that it is easier to the absorb material.